Magneto hipertermia in vitro em células hek293t utilizando nanopartículas de óxido de ferro magnéticas com diferentes recobrimentos - Shigeyosi, Willian Takemitsu (Universidade Federal de São Carlos, 2017)
One of the largest challenges on medicine has been developing treatments for several types of cancer. Moreover, conventional treatments for cancer such as chemotherapy and radiotherapy have been presenting undesirable secondary effects. As an alternative, nanomaterials have the premise of improving and creating a new route of treatment and diagnosis. Currently, iron oxide nanoparticles are strongly studied especially because of their ability to produce heat when they are subjected to an alternating magnetic field. The mechanism of induced heating via external magnetic field is called magnetic hyperthermia and, through this mechanism, it becomes possible to make the biothermic applications and use drug delivery system. The advantage of using a magnetic nanomaterial comes from the unusual feature knew as superparamagnetism. The superparamagnetic systems does not present spontaneous magnetization nor coercive field therefore their magnetization curves do not present hysteresis losses. Therefore, the motivation of this work comes from the need for biophysical information regarding the hyperthermic magneto treatment of these nanomaterials in human tissues. Thus, the aim of this thesis is to deal with fundamental aspects related to the behavior of the Fe3O4 nanoparticles in cell media during hyperthermia. In this context, it will be approaching some questions about the use of iron oxide nanoparticles with distinct types of coatings. Discussing the advantages and disadvantages of each coating according to its physico-chemical characteristics as well as its cytotoxicity. In addition, this work approaches the hyperthermic magneto potential of these superparamagnetic coated nanoparticles by comparing their respective performances in the treatment of human’s embryonic kidney cells HEK293T. Through the development of this work it was observed that for a good bioapplicability’s samples must present a low cytotoxicity, in this case the coatings formed by surfactants like centrimonium bromide and sodium dodecyl sulfate presented a high rate of cellular mortality not being indicated for the treatment. Finally, the potential of magnetic hyperthermia for a biocompatible nanomaterial should be evaluated, in this case the best results associated to hyperthermia treatment were obtained for nanoparticles coated with chitosan, polyethylene glycol and PEGylated phospholipid.
Magneto hyperthermia in vitro on hek293t cells using magnetic iron oxide nanoparticles with different coatings
Keywords: Hipertermia; Superparamagnetismo; Nanopartículas de óxido de ferro; SAR; Hyperthermia; Superparamagnetism; Iron oxide nanoparticles; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::MATERIAIS MAGNETICOS E PROPRIEDADES MAGNETICAS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::PROPRIEDADES TERMICAS DA MATERIA CONDENSADA